A Study of Slang Words in the Album of “My World 2.0” by Justin Bieber - Widyareka, Risa; Putu Desi Anggerina Hikmaharyanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
Abstract This study is entitled “A Study of Slang Words in the Album of My World 2.0 by Justin Bieber”. The album was chosen because it has slang words as the data source, the album has songs that are the most popular album by Justin Bieber and the most listened to songs by people around the world. The observation method was used to collect data and the qualitative method was used to collect the data clear and well-organized description of the problems. The theory used was found in Kipfer & Chapman (2007) was applied in the analysis of the types of slang words. Based on the result of Album of My World 2.0 by Justin Bieber draw the conclusion that the primary slang words and secondary slang words are the only types in this study.